Palma forrageira: morfometria e silagem na forma de ração completa - Farias, Lídia Lidiane (2018)
Due to irregular rainfall in the semiarid region, the production of animal feed is one of the greatest challenges in the dry season, where forage palm has an excellent potential for use in animal feed.The objective of this work was to evaluate the initial growth, by means of morphometric and morphogenic characteristics of the small palm and elephant ear varieties in the Brejo Paraibano, as well as to evaluate the fermentative pattern and losses of small palm silages in the form of complete with the inclusion of forage plants. Two experiments were conducted in the city of Areia-PB. In the first, evaluations of the morphometric and morphogenic characteristics of the small and elephant palms were performed.In the second one, silage was made using the small variety, where the plots consisted of five sources (Tifton Grass Hay, Catingueira, Maniçoba, Pereiro and Capim Elefante) in two opening times of the silos (30 and 60 days) to evaluate the fermentative pattern and losses. For the morphometric characteristics, it was verified that there was a significant difference in the parameters cladodium width (CL), cladode perimeter (PC), plant height (AP) and cladode number (NC), where elephant ear variety presented higher LC (11,5 cm) and PC (39,1 cm) and the smallest palm AP (32,4 cm) and NC (3,23). Regarding the morphogenic characteristics, there was a significant difference in the rate of appearance of cladodium (TapC), which was higher in the small palm (0,040 clad/dia-1). The area of cladodium (AC) was higher in the elephant ear. For the ensilage characteristics, adequate pH values were found in the treatments with Tifton Hay (4,17) and Catingueira (4.11) at 30 days of silage, where the other treatments presented values above the recommended maximum, despite this , there was no break in stability. In relation to the recovery of dry matter (P = 0.001) and ammoniacal nitrogen (P <0.001) there was interaction Treatment x Time. However, for the effluent losses variable, there was only effect for silage time, with losses greater than 60 days (6,56%). It was concluded that the initial growth of the small palm is superior to that of the elephant ear and that the complete feed containing palm forage presented better quality at 30 days of silage.